Model Pembaharuan Pendidikan Islam dari Masa Klasik sampai Modern - Sarwadi (IIQ An Nur Yogyakarta, 2023)
There were constant changes in Islamic education. Education had felt generations since the early centuries of Islam and continues to do so today. To meet the demands of society at that time, the concept of Islamic education continued to experience renewal. From the period of the Companions of the Prophet to the 20th century, this study seeked to examine the literature on the renewal of the Islamic renewal thought model. This study method used literature research by examining several primary and secondary sources. The Tathbiqi educational model was where the Islamic education model which was known since the reign of the caliph Abu Bakar as a Shia began. The renewal lasted until the tajdidi period, when Muhammad Abduh and Rashid Ridha pioneered the reform of Islamic education.